2015
DOI: 10.1007/s00192-015-2632-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hyperpolarization-activated cyclic nucleotide-gated channel expression and activity in bladder interstitial cells of Cajal from rats with detrusor overactivity

Abstract: All HCN channel isoforms were highly expressed in bladders from the DO group, which was correlated with increased Ih currents in DO ICCs, suggesting that the HCN channels might play an important role in the pathological processes of DO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The effect of ZD7288 on the concentrations tested here agree with previously reported results [ 12 ] as well with the reported IC50 of ZD7288 for HCN channels, which is in the range of 0.2 μM for heart [ 20 ] and1.8 μM for brain neurons [ 21 ]. There is a risk that higher concentration of ZD7288 (50 μM) used in recent bladder strip studies [ 13 , 22 ] may receive confounding contribution from inhibition of other channels as ZD7288 can block T-type Ca 2+ channels with an IC50 of 100 μM [ 23 ]. ZD7288 at lower dose levels, which are closer to the reported IC50 of ZD7288 for HCN channels, increases the amplitude and frequency of spontaneous contractions.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ZD7288 on the concentrations tested here agree with previously reported results [ 12 ] as well with the reported IC50 of ZD7288 for HCN channels, which is in the range of 0.2 μM for heart [ 20 ] and1.8 μM for brain neurons [ 21 ]. There is a risk that higher concentration of ZD7288 (50 μM) used in recent bladder strip studies [ 13 , 22 ] may receive confounding contribution from inhibition of other channels as ZD7288 can block T-type Ca 2+ channels with an IC50 of 100 μM [ 23 ]. ZD7288 at lower dose levels, which are closer to the reported IC50 of ZD7288 for HCN channels, increases the amplitude and frequency of spontaneous contractions.…”
Section: Discussionmentioning
confidence: 99%
“…HCN channels were thought to be the key modulators of bladder ICC-LCs with respect to the conduction of bladder pacemaker activity. 12 In addition, HCN channel expression and function were significantly altered in the bladder ICC-LCs of diabetic cystopathy and detrusor overactive (DO) bladders with partial bladder outlet obstruction (PBOO), 21 , 22 suggesting that HCN channels in bladder ICC-LCs are involved in regulating bladder function in physiological and pathological conditions. To our knowledge, the role of HCN channels in bladder ICC-LCs in cystitis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…21 In bladder overactivity, developed in a rat model following partial bladder outlet obstruction, it was shown that the physiological functioning of ICCs changes and the expression of the HCN channels in bladder ICCs significantly increases. [22][23][24] These findings suggest that the HCN channels and ICCs might play an important role in the pathogenesis of detrusor overactivity. Thus, the involvement of the HCN channels is another possible mechanism mediating the inhibition of cholinergic agonist-induced bladder contraction by ivabradine.…”
Section: Discussionmentioning
confidence: 85%